The Impact of Education Personnel Performance on the Quality of Academic Services at Madrasa Tsanawiyyah - Anisa Putri, Diana Rizkika; Yetri, Yetri; Hijriyah, Umi (Universitas Islam Negeri Raden Intan Lampung, 2024)
The existence of education personnel or school administration in the learning process is very necessary as one of the components of the learning process. Duties and functions are not usually carried out by educators because administrative work is administrative in nature which is subject to special rules. Often times quality improvement is always echoed with teachers and students, in fact, increasing the quality of education quality is almost unheard of involving also improving the quality of administrative staff who are part of the education workforce. As an educational institution that offers service products, schools must be able to offer and convince the public that the school is the right educational institution. The increasing need for education among the community both formally and non-formally is an encouragement for them to send their children to schools that have good quality and service. This study aims to determine whether there is a significant influence between the performance of education personnel on the quality of academic services at MTs Negeri 2 Bandar Lampung. The approach used is quantitative by using various validity tests, reliability tests, prerequisite tests and also deeper hypothesis testing. The methods used consist of questionnaires, observation, and documentation with non-parametric statistical analysis techniques on ordninal data. The results show that there is a significant influence between the performance of education personnel on the quality of academic services at MTs Negeri 2 Bandar Lampung.